Principles of occupational medicine: an educational case study of hazards and risks for Dr “Indiana” Jones - Thomas C. Erren; Christopher Dietrich; Jonas Wallraff; Florian Glenewinkel; Andreas Pinger; Philip Lewis (Journal of Occupational Medicine and Toxicology)
Abstract Background Understanding the nature and consequences of hazards and risks in the workplace is critical to protecting people from harm. Educational case study We review the fictional example of “Indiana” Jones as an educational vector to illustrate principles of occupational medicine in real-world scenarios. Conclusion After reviewing the Jones saga regarding potential hazards (physical – biological – chemical – psychosocial), we provide a practical outlook on the workplace health for readers with a non-occupational medicine background.